Kembara Prihatin@Bumi Kenyalang 2.0 Travel Programme strengthens collaboration between UMPSA, IKM Bintulu, and Alumni - Nor Salwana, Mohammad Idris (UMPSA, 2024)
BINTULU, 17 August 2024 – Living with adoptive families and working together to make the programme a success gave 24 volunteers from the UMPSA Foundation Squad and 13 volunteers from the MARA Skills Institute (IKM) an opportunity to contribute to the Ukit community at the Uma Ukit Longhouse in Sungai Asap, Bintulu, Sarawak.